Policy Reform, Adjustment Costs, and Investment : With Activity of Local Investors as a Signal - Johnson, Omotunde (Washington, D.C. : International Monetary Fund, 1997)
Adjustment assistance is provided to local investors responding to policy reform and facing adjustment costs, to facilitate their activity-a signal to foreign investors about the profitability of investing in the local economy. The government, in providing assistance, maximizes its utility subject to its budgetary constraint, taking into account the utility forgone in alternative uses of budgetary funds. Foreign investors use the signal to update beliefs about investors in the local economy and compute the expected return from investing in the country. The investment response of foreign investors depends on the expected return so computed relative to the expected returns in their alternative investments worldwide.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet